PENGARUH PENGHARGAAN INTRINSIK DAN PENGHARGAAN EKSTRINSIK TERHADAP KEPUASAN KERJA KARYAWAN PERUMDA BPR PUSAT MAJALENGKA - Nita Hernita (Program Studi Akuntansi Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2022)
Research was conducted on employees of Perumda BPR Pusat Majalengka. Target of this research is to identify intrinsic rewards and extrinsic rewards to employee job satisfaction, and how much influence the intrinsic rewards and extrinsic rewards to employee job satisfaction. The method used is by using descriptive analysis and verification techniques. The sample is this study were 45 peoples using saturated sampling techniques. Data collection are the questionnaires. Testing is done with the data instrument validity and reliability testing, while data anlysis is a classic assumption test, multiple regression test, determination, and hypothesis testing with SPSS 21 Version. Based on research results to the variable intrinsic rewards, extrinsic rewards, and employee job satisfaction variables included in the high category. Furthermore, based on verifikatif analysis of intrinsics rewards and extrinsics rewards have a positive and significant impact on employee job satisfaction either partially or simultaneously